2016
DOI: 10.1186/s12263-016-0527-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for nutrient intake with focus on alternative sampling techniques

Abstract: Biomarkers of nutrient intake or nutrient status are important objective measures of foods/nutrients as one of the most important environmental factors people are exposed to. It is very difficult to obtain accurate data on individual food intake, and there is a large variation of nutrient composition of foods consumed in a population. Thus, it is difficult to obtain precise measures of exposure to different nutrients and thereby be able to understand the relationship between diet, health, and disease. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 215 publications
(257 reference statements)
0
22
0
Order By: Relevance
“…Finally, Burton et al [ 118 ] reported an increased in faecal Bifidobacteria after consumption during 2 weeks of a non-fermented milk acidified with D-(+)-glucono-δ-lactone but not after the consumption of yoghurt. In this field, it is, however, important to keep in mind that there are different methods and no standard protocols for assessing bacterial proportions in faecal samples [ 123 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Burton et al [ 118 ] reported an increased in faecal Bifidobacteria after consumption during 2 weeks of a non-fermented milk acidified with D-(+)-glucono-δ-lactone but not after the consumption of yoghurt. In this field, it is, however, important to keep in mind that there are different methods and no standard protocols for assessing bacterial proportions in faecal samples [ 123 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the compounds mentioned in this section have been linked to yogurt consumption, none of them qualify as a biomarker of yogurt intake; these metabolites are widely distributed in several food sources, compromising their specificity with respect to yogurt intake. These compounds can more likely be used as biomarkers of nutrient intake, nutritional status or microbiota integrity than as biomarkers of specific food consumption, as recently reviewed by Holen and co-workers [ 123 ].…”
Section: Resultsmentioning
confidence: 99%
“…52,53 To improve the estimation of protein intake, studies including data on biomarkers of energy and protein intake, for example 24 h urine nitrogen, are recommended. 19,44,54,55 Implications for clinical practice…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…DBS offer a simpler way of storing and acquiring blood samples and have been used for disease surveillance, drug resistance analyses, clinical and pre‐clinical pharmacokinetic studies, population studies, and global newborn screening of metabolic diseases since the 1960s . DBS samples have many benefits compared to standard serum and plasma samples in that collection is less invasive for the patient (normally a finger or heel prick), storage and transport costs are lower, and sampling does not require a health personnel so it can be performed anywhere . These benefits are of particular interest for studies in remote locations and those having large cohorts where thousands of samples are collected and must be stored.…”
mentioning
confidence: 99%